Implementing Project Management Integrated with ITIL: Case Study in a Fast-Moving Consumer Goods Company - Teguh Raharjo; Ni Wayan Trisnawaty; Rina Yuniarti; Gentri Adiningtyas (The Indonesian Journal of Computer Science, 2024)
At the last phase of an IT project, it will transfer to the operations team. It is critical to ensure the change management process integrated between project and operations is working smoothly. The study highlights lessons from implementing project management integrated with ITIL. This research is conducted on a multinational Fast-Moving Consumer Goods (FMCG) company that has already implemented project management integrated with ITIL. The study adopts PMBOK and ITIL frameworks, previous studies, and guided interviews, which are then analyzed using socio-technical aspects. This research can enrich existing literature, especially regarding IT project management and service areas. The study concludes that implementing project management integrated with ITIL brings a steadier process to IT projects. One of the socio-technical aspects changed, and the others should be adjusted. Each implementation phase results in different Socio-Technical Systems (STS) components. Nevertheless, as a whole implementation project, the company has already completed all components required.